1973
DOI: 10.1002/jmor.1051400404
|View full text |Cite
|
Sign up to set email alerts
|

The photoreceptors of the “four‐eyed” fish, Anableps anableps L

Abstract: The photoreceptors of the adult Anableps anableps have been investigated by light microscopy, scanning and transmission electron microscopy. The fish is a surface swimmer and the eye is divided by the water meniscus. In general, the photoreceptors (rods, single cones, and double equal cones) resemble those of other vertebrates, but there are several unusual features: (1) The outer segment discs of the double cones differ in the two members. (2) All cones have a prominent accessory outer segment derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 68 publications
3
32
0
Order By: Relevance
“…for the dystrophic lake populations were 14.4±0.95nm and 9.3±1.8nm (N=63 cones, 6 fish), and 14.7±0.89nm and 9.2±1.6nm (N=75 cones, 8 fish) for the transplanted populations. These numbers, which are in the range reported for other fishes (Borwein and Hollenberg, 1973;Collin et al, 1996), indicate no changes in outer segment morphology as a result of transplantation.…”
Section: Cone Morphology and Ultrastructuresupporting
confidence: 75%
“…for the dystrophic lake populations were 14.4±0.95nm and 9.3±1.8nm (N=63 cones, 6 fish), and 14.7±0.89nm and 9.2±1.6nm (N=75 cones, 8 fish) for the transplanted populations. These numbers, which are in the range reported for other fishes (Borwein and Hollenberg, 1973;Collin et al, 1996), indicate no changes in outer segment morphology as a result of transplantation.…”
Section: Cone Morphology and Ultrastructuresupporting
confidence: 75%
“…Membrane-bound and filled with a dense amorphous matrix that is insoluble in organic solvents, these globules appear to be mature ellipsosomes as described in the cones of a number of teleost fishes [Borwein and Hollenberg, 1973;MacNichol et al, 1978;Nag and Bhattarcharjee, 1995]. An increase in the density of mitochondrial cristae surrounding the ellipsosome, the similar osmiophilic staining of both structures and the putatively colorless nature of the ellipsosome suggest that it is of mitochondrial origin.…”
Section: Photoreceptorsmentioning
confidence: 81%
“…Of mitochondrial origin, similar structures have been described in the cone photoreceptors in a number of vertebrate classes, including teleosts [Walls, 1942;Ishikawa and Yamada, 1969;Borwein and Hollenberg, 1973;Kunz and Regan, 1973;Kunz and Wise, 1973;Anctil and Ali, 1976;Nag andBhattacharjee, 1989, 1995;Nag, 1995] and mammals [Knabe et al, 1997] including primates [Bowmaker, 1991]. Although the photoreceptors in M. mordax have not been definitively characterized as rod-like, such confirmation in the future would mean that M. mordax provides the first report of an ellipsosome within a rod.…”
Section: Functional Significance Of An Ellipsosome-bearing Photoreceptormentioning
confidence: 92%
See 1 more Smart Citation
“…viously in the paired cones of other teleost species (Berger, 1967;Borwein and Hollenberg, 1973;Cantino et al, 1986) were never observed in rods or SCs. The fundamental rhombic pattern in stretched retina was evident in the electron micrographs (dotted lines, Fig.…”
Section: New Cones In Stretched Retinamentioning
confidence: 97%